2020
DOI: 10.1002/jtr.2431
|View full text |Cite
|
Sign up to set email alerts
|

The effect of place personality on resident welcoming tourist through positive and negative impacts of tourism

Abstract: The aim of this study is to identify residents' place personality attitudes regarding the place in which they live and to determine the effects of this attitude on attitudes to positive and negative impacts of tourism and residents' welcoming of tourists. Results of the analysis reveal that the sincerity and excitement dimensions of place personality affected residents welcoming tourists through attitudes to positive impacts of tourism; however, the sophistication dimension affected residents welcoming tourist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
(216 reference statements)
0
0
0
Order By: Relevance
“…To determine if the data followed a normal distribution, we examined skewness and kurtosis values, following the methodology outlined by Kline [48]. AMOS results indicated that each item had a skewness and kurtosis value below 2 and 3, respectively, which is generally considered acceptable [38]. Additionally, the data were examined for potential common method bias (CMB).…”
Section: Cfa and Sem Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine if the data followed a normal distribution, we examined skewness and kurtosis values, following the methodology outlined by Kline [48]. AMOS results indicated that each item had a skewness and kurtosis value below 2 and 3, respectively, which is generally considered acceptable [38]. Additionally, the data were examined for potential common method bias (CMB).…”
Section: Cfa and Sem Resultsmentioning
confidence: 99%
“…Spanning nearly two decades, the emotional solidarity (ES) construct and its accompanying theoretical framework have been employed with regularity in the tourism literature [17,[35][36][37][38]. According to Woosnam [16], the theory examines the affective bond between locals and visitors, and the formers' interactions, shared values, and behaviors influence how well they get along with the latter.…”
Section: Residents' Attitudes About Tourism and Emotional Solidarity ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, the objectives and analysis techniques posed increased in sophistication (e.g., [28][29][30][31][32][33][34][35]). Nowadays, the study of causal relationships which could explain residents' attitudes is a priority (e.g., [3,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]). There are also studies more focused on the consequences of residents' attitudes [52][53][54].…”
Section: Introductionmentioning
confidence: 99%